2005
DOI: 10.1111/j.1440-1746.2005.03726.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of vascular endothelial growth factor, fibroblast growth factor‐2 and endostatin in patients with hepatocellular carcinoma

Abstract: The results suggest that VEGF, FGF-2, and endostatin concentrations are elevated prior to the emergence of HCC and that the distribution of VEGF changes dynamically during the development of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 23 publications
(23 reference statements)
0
53
0
4
Order By: Relevance
“…FGF2, VEGF, and PDGFB are potent mitogenic and angiogenic factors and stimulate tumor growth (45). Expression of VEGF and FGF2 is altered in patients with HCC and, interestingly, VEGF and FGF2 concentrations are elevated before the emergence of HCC (46). By maintaining high levels of expression of these factors on hepatocytic differentiation, mTOR may accelerate abnormal proliferation and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…FGF2, VEGF, and PDGFB are potent mitogenic and angiogenic factors and stimulate tumor growth (45). Expression of VEGF and FGF2 is altered in patients with HCC and, interestingly, VEGF and FGF2 concentrations are elevated before the emergence of HCC (46). By maintaining high levels of expression of these factors on hepatocytic differentiation, mTOR may accelerate abnormal proliferation and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that FGF5 overexpression has been associated with a number of tumor cell lines (lung, esophagus, melanoma, colon, and prostate; ref. 23), and in hepatocellular carcinomas (HCC), the upregulation of FGF2, 8, 17, and 18 initiates autocrine growth stimulation, cell survival, and neoangiogenesis (24)(25)(26)(27). Further, HCC has been found to develop in transgenic mice overexpressing the hormonal FGF19 (28), and FGF19 is found on an amplicon on chromosome 11q that also invariably contains the adjacent FGF3, FGF4, and Cyclin D1 (CCND1) genes.…”
Section: Autocrine and Paracrine Signalingmentioning
confidence: 99%
“…FGF signaling regulates fundamental cellular developmental processes (12), and aberrant FGF signaling is associated with tumorigenesis (8,(11)(12)(13). In addition, FGF-2 has potent effects on vascular endothelial cell proliferation (14), and levels are elevated in tumors and/or serum in patients with a variety of cancers, including HCC (15)(16)(17)(18). Recent clinical data suggest that upregulation of alternate proangiogenic signaling pathways, such as the FGF signaling pathway, may play a role in the development of resistance with anti-VEGF therapies (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%